1983
DOI: 10.2307/3544109
|View full text |Cite
|
Sign up to set email alerts
|

Species-Energy Theory: An Extension of Species-Area Theory

Abstract: This paper defines the relationships between geographical location (which determines macroclimatic differentiation and reflects the history of the vegetation), soils (which determine hydrolytic acidity, degree of base saturation and organic carbon content), and selected characteristics of vegetation (species richness, herb layer biomass, moss layer biomass) in one type of forest community, namely, pine forests of the Vaccinio-Piceetea class. The study area covers the major part of the European domain of pine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

87
1,124
16
18

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,253 publications
(1,245 citation statements)
references
References 39 publications
87
1,124
16
18
Order By: Relevance
“…In 1102 summary, the two products aboveground biomass map and biomass change will capture 1103 the successional state and the rate of succession, and the underlying mechanism of 1104 successional trajectory as shown in Figure 9b. The occurrence of such patterns has been 1105 documented for several different mature forest systems and is consistent with the mosaic 1106 dynamics of mature forests (Whitmore 1974, Knight 1975, Hartshorn 1978, Raup 1964, 1107White 1979, and Oliver 1981 (Wright 1983) and over landscapes at 1119 regional scales by topography (Burnett et al, 1998;Thompson and Brown, 1992). 1120…”
Section: Required Biomass Change Measurement Capabilities 1043supporting
confidence: 57%
“…In 1102 summary, the two products aboveground biomass map and biomass change will capture 1103 the successional state and the rate of succession, and the underlying mechanism of 1104 successional trajectory as shown in Figure 9b. The occurrence of such patterns has been 1105 documented for several different mature forest systems and is consistent with the mosaic 1106 dynamics of mature forests (Whitmore 1974, Knight 1975, Hartshorn 1978, Raup 1964, 1107White 1979, and Oliver 1981 (Wright 1983) and over landscapes at 1119 regional scales by topography (Burnett et al, 1998;Thompson and Brown, 1992). 1120…”
Section: Required Biomass Change Measurement Capabilities 1043supporting
confidence: 57%
“…That geographical variation in species richness correlates positively with energy availability was recognised in the 19th century (Wallace, 1878) and it has frequently been suggested that spatial variation in energy availability controls species richness (Hutchinson, 1959 ;Connell & Orias, 1964 ;Leigh, 1965 ;MacArthur & Pianka, 1966 ;Rohde, 1978;Schall & Pianka, 1978;Rickerson & Lum, 1980). Wright (1983) built upon such studies to propose the species-energy theory, that energy sets an upper limit to species richness. Interest in species-energy relationships grew during the 1980s and 1990s (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, lake area always contributed the most to the fish species richness patterns, since that large area could support more fish species to coexist, say species richness -area hypothesis (Wright, 1983). Over the last two decades, numerous of case studies in Africa, US, Canada, Tropical Asia and Europe all verified the species richness-area patterns in a broad scale (Amarasinghe and Welcomme, 2002).…”
Section: Prediction and Determinants Of Fish Species Richness In Chinmentioning
confidence: 85%